Biological treatments for pediatric Netherton syndrome - Pontone, Matteo; Giovannini, Mattia; Filippeschi, Cesare; Oranges, Teresa; Pedaci, Fausto Andrea; Mori, Francesca; Barni, Simona; Barbati, Federica; Consonni, Filippo; Indolfi, Giuseppe; Lodi, Lorenzo; Azzari, Chiara; et al. (Frontiers in Pediatrics, 2022)
Netherton syndrome (NS) is a rare and potentially life-threatening genetic skin disease responsible for skin inflammation and scaling, hair abnormalities and severe allergic manifestations. NS is caused by loss-of-function variants in Serine Peptidase Inhibitor Kazal-Type 5 (SPINK5), encoding the serine protease inhibitor LEKTI. NS patients have a profound skin barrier defect caused by unopposed kallikrein-related proteases activity (KLKs). They develop severe skin inflammation with eczematous-like lesions and high serum IgE levels. Multiomics studies have revealed that the IL-17/IL-36 pathway is the most predominant upregulated pathway in NS. It is associated with a Th2 signature with complement activation in the ichthyosis linearis circumflexa subtype, and with interferon and Th9 activation in the scaly erythrodermic form. Several case reports proved the efficacy of different biotherapies targeting IL-17A, IL-12/IL-23, IL-4R and IL-13R, TNF-a and IL-1β in pediatric NS patients. Intravenous immunoglobulins (IVIG) have also shown efficacy. These studies showed no severe side effects. At present, IL-17 blockade seems to be the most efficient treatment, but case reports remain limited with small numbers of patients and no placebo-control. Additional pathways must also be explored, and more efficient strategies could be used to block IL-17 and IL-23 pathways. In the future, the combination of specific strategies aiming at repairing the initial skin barrier defect could potentiate the efficacy of biologics. The current reports suggest that biological therapy is safe and often effective at pediatric age. However, controlled clinical trials that include a larger number of patients need to be conducted to reach more reliable conclusions.